Methotrexate toxicity-an alarming bell! - Agarwal, Pooja; Chaudhari, Snehal V.; Baxi, Kalgi; Neazee, Sabha; Soneji, Sohini; Shah, Malhar J. (International Journal of Research in Dermatology, 2023)
Since its introduction in 1951, methotrexate (MTX) has been widely used as the primary anti-psoriatic agent. However, unsupervised dosing by patients or concurrent use of excessive nonsteroidal anti-inflammatory drugs (NSAIDs) can lead to toxicity. Gastrointestinal symptoms are the most commonly observed manifestations, followed by cutaneous toxicity. In this retrospective study conducted at a tertiary care center in Gujarat, data from patients admitted for MTX toxicity between April 2017 and December 2019 were analyzed. A detailed history, including dosage, duration, signs and symptoms, investigations, treatment, and outcomes, was collected and evaluated. The study included 12 hospitalized patients (aged 35-70 years) with MTX toxicity. Among them, 10 patients had psoriasis, 1 had psoriatic arthritis, and 1 had rheumatoid arthritis with discoid lupus erythematosus. Eleven patients had taken daily oral MTX for one week along with painkillers, while one patient had taken an unknown amount without undergoing any investigations. Mucosal ulceration was observed in all cases, and skin necrosis was seen in 2 patients. Hematological investigations revealed myelosuppression in all patients, with altered renal function in 1 patient. Leucovorin (15 mg/ml) was administered to all patients, resulting in improvement for 10 patients, but 2 patients experienced persistent myelosuppression and succumbed to the toxicity. This study emphasizes the importance of pre-treatment investigations, proper monitoring, and strict avoidance of self-administration when administering MTX. Additionally, the co-administration of drugs such as NSAIDs should be judiciously managed. Folinic acid has shown usefulness in cases of MTX toxicity and overdose. In summary, this study underscores the significance of careful administration and monitoring of MTX, along with the avoidance of self-dosing. It highlights the need for judicious use of co-administered medications, and emphasizes the utility of folinic acid in managing MTX toxicity and overdose.